A STUDY OF STUDENTS’ ANXIETY IN SPEAKING - Ardhea Rosana Putri; Evi Zulida; Rahmiati Rahmiati; Surya Asra; Fadlia Fadlia (Journal of Education, Linguistics, Literature and Language Teaching, 2020)
This study aimed to describe about the factors cause students’ anxiety in speaking English and the students strategies to cope the anxiety in speaking English in Class X of SMAN 5 Langsa of 2019-2020 year as participants. Any 21 students as participants that researcher take by purposive sampling. Participants in this study just 3 students in every class.The Method used in this study was descriptive qualitative. The data were through structured Interviews and classroom observations. The data were in the interview transcripts. The result of this study describe three factors that cause students’ anxiety in speaking English. The first factors is Self Perception of students that always feel English is difficulty to Learn and speak. The second factor is Class Condition of Performance make students got anxiety when they speak in front of friends and teacher. The third factor in students’ Anxiety in speaking English is Fear of Making Mistakes. The result of this study found that there are three strategies that students used to cope the anxiety in speaking English. The first strategies is Preparation, eight students did preparation always felt better before speaking English. The second is Positive thinking, there are seven participants think that positive thinking can cope the anxiety in speaking English. The last strategies is Relaxation, as many as five students take this strategies if students feel anxiety and failed speaking english. Keywords: Anxiety, Speaking